1996
DOI: 10.1016/s0022-2143(96)90164-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with cholesterol-rich liposomes induces anti-cholesterol antibodies and reduces diet-induced hypercholesterolemia and plaque formation

Abstract: Immunization of rabbits with a protein-free formulation consisting of liposomes containing 71% cholesterol and lipid A as an adjuvant induced anticholesterol antibodies that caused complement-dependent lysis of liposomes lacking lipid A. The antibodies, immunoglobulin G (IgG) and immunoglobulin M (IgM), also recognized nonoxidized crystalline cholesterol as an antigen by enzyme-linked immunosorbent assay (ELISA). The effects of immunization against cholesterol on elevations in serum cholesterol and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…A putative role of ACHAs in atherosclerosis, induced by a cholesterol-rich diet, can be postulated from results of experiments with rabbit models (7).…”
mentioning
confidence: 99%
“…A putative role of ACHAs in atherosclerosis, induced by a cholesterol-rich diet, can be postulated from results of experiments with rabbit models (7).…”
mentioning
confidence: 99%
“…This hypothesis is supported by the synthesis of specific antibodies against cholesterol upon injection of cholesterol-rich liposomes in rabbits and mice [32,33] . These antibodies recognize non-oxidized crystalline cholesterol [32] , and analyses by solid-phase ELISA revealed that human sera contain varying levels of naturally occurring autoantibodies to cholesterol [34] . Similarly, humans might synthesize and secrete specific IgA antibodies to cholesterol into bile.…”
Section: Discussionmentioning
confidence: 87%
“…Several other groups of investigators subsequently reported similar atheroprotective effects by active immunization with cholesterol-rich liposomes in cholesterol-fed rabbits [Alving et al 1996], MDAmodified LDL in apoE(-/-) mice [George et al 1998b] or with plaque homogenates or MDAmodified LDL in apoE(-/-) mice [Zhou et al 2001].…”
Section: Active Immunization With Antigens Related To Low-density Lipmentioning
confidence: 80%